2000
DOI: 10.1021/es990773r
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium Interactions with Mackinawite:  Retention Mechanisms and the Role of pH

Abstract: The reactive iron monosulfides including mackinawite are known for their ability to scavenge trace metals. Oxidation and reduction reactions in sediments and the types of metal bonding with mackinawite determine both the stability of the metal bonds and the susceptibility of the material to oxidation. Metal retention is important because it influences the availability of toxic metals to aquatic organisms. In this study, Pb and Cd interactions with mackinawite were investigated, and two major retention mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 21 publications
6
42
0
1
Order By: Relevance
“…The mackinawite in Fig. 1B fits the description as noted by others [24]. Previous studies [22] have demonstrated that the primary FeS precipitate formed from the reaction between Fe(II) and S(-II) in aqueous solutions at ambient temperatures and pressures is nanoparticulate stoichiometric mackinawite, Fe 1.00±0.01 S, thus the prepared FeS should be mackinawite.…”
Section: Properties Of Fessupporting
confidence: 78%
See 1 more Smart Citation
“…The mackinawite in Fig. 1B fits the description as noted by others [24]. Previous studies [22] have demonstrated that the primary FeS precipitate formed from the reaction between Fe(II) and S(-II) in aqueous solutions at ambient temperatures and pressures is nanoparticulate stoichiometric mackinawite, Fe 1.00±0.01 S, thus the prepared FeS should be mackinawite.…”
Section: Properties Of Fessupporting
confidence: 78%
“…FeS has a high adsorptive capacity for various divalent metals [23][24][25][26][27], but in-depth studies of Hg(II) sorption to FeS are rare. Metals whose sulfide phases are less soluble than FeS exhibit an increasing surface affinity with decreasing solubility [27].…”
Section: Introductionmentioning
confidence: 99%
“…Similar drop in pH with Cd 2+ loading was observed by Coles et al 13 and Parkman et al 14 The amount of iron released accompanying the sorption of Cd 2+ ions is given in Table 2. As observed, the amount of iron released from the surface increases with the increase in temperature.…”
Section: supporting
confidence: 81%
“…The low values of n point towards the possibility of the formation of mixed sulphide of Cd and Fe, as suggested elsewhere. 2,13,14 This is also confirmed by the absence of iron release from the surface at 303 K, as shown in Table 2.…”
Section: supporting
confidence: 70%
“…Due to its chalcophilic nature, FeS can sequester a range of divalent metals (e.g., Mn(II), Co(II), Ni(II), Cd(II), Hg(II), and Pb(II)) by forming surface complexes, insoluble metal sulfides, and solid solutions Morse and Arakaki, 1993;Coles et al, 2000;Billon et al, 2001;. This phase is also capable of converting Cr(VI), a toxic and highly mobile form of Cr, to the very insoluble and less toxic Cr(III) (Patterson et al, 1997;Boursiquot et al, 2002;Mullet et al, 2004).…”
Section: Introductionmentioning
confidence: 99%